2020
DOI: 10.1371/journal.pntd.0008700
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, practices of/towards COVID 19 preventive measures and symptoms: A cross-sectional study during the exponential rise of the outbreak in Cameroon

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (COVID 19) has plagued the world with about 7,8 million confirmed cases and over 430,000 deaths as of June 13 th, 2020. The knowledge, attitude, and practices (KAP) people hold towards this new disease could play a major role in the way they accept measures put in place to curb its spread and their willingness to seek and adhere to care. We sought to understand if: a) demographic variables of Cameroonian residents could influence KAP and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
119
19
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 6 publications
43
119
19
8
Order By: Relevance
“…Throughout their academic studies, scholars have laid emphasis on the fact that knowledge is exceedingly important as it has a direct bearing on the attitude that people form towards something. 6,31,35 The findings of the study corroborated the foreboding fact and further found that international students had enough and adequate information which positively increased their good knowledge regarding the causes, spread, and symptoms of COVID-19, with have high scores of up to 98%. However, the results indicated that there was a significant mean score difference between age groups (P<0.01), of which the group of <20 years had lower mean scores as compared to other groups, and major of study (P=0.015), where those in engineering majors and other studies had lower mean scores as compared to medical and agriculture majors.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Throughout their academic studies, scholars have laid emphasis on the fact that knowledge is exceedingly important as it has a direct bearing on the attitude that people form towards something. 6,31,35 The findings of the study corroborated the foreboding fact and further found that international students had enough and adequate information which positively increased their good knowledge regarding the causes, spread, and symptoms of COVID-19, with have high scores of up to 98%. However, the results indicated that there was a significant mean score difference between age groups (P<0.01), of which the group of <20 years had lower mean scores as compared to other groups, and major of study (P=0.015), where those in engineering majors and other studies had lower mean scores as compared to medical and agriculture majors.…”
Section: Discussionsupporting
confidence: 76%
“…As a results this research is in agreement with other studies that found that a lot of people practice good preventive and control practices given by their authorities. 22,31,41 Furthermore, this study found that there was a positive correlation between attitude and adherence to preventative practices against COVID-19, which indicated that if people possessed good attitudes towards pandemics like COVID-19 they were more likely to conform to all the preventive measures against COVID-19. However, there was no significant relationship between knowledge and attitude and practices, which differs with other studies which were conducted on the same topic and other topics.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The continuous rise in the number of cases and the overall good knowledge, attitude, and practice justify a further investigation to determine the effectiveness of the measures put in place to control the spread of this disease. 11 Understanding the public attitudes, beliefs, and behaviors is important and significant during this pandemic situation. Encouraging the public for these behaviors suggests a chance to normalize safe practices and promote a continued use of these and other recommended personal protective behaviors to reduce the further spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%